Effectiveness of Mediterranean diet on diabetic control and cardiovascular risk modification among patients with type 2 diabetes mellitus in Oman: a study protocol - Salim, AlAufi Najwa; Chan, Yoke Mun; Chin, Yit Siew; Ahmad, Norliza; Mohd Yusof, Barakatun Nisak; I Waly, Mostafa (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: In the recent years, there is remarkable increased in the prevalence of Type 2 Diabetes Mellitus (T2DM) in Middle East countries including Oman. There is good evidence that Mediterranean Diet (MedDiet) is effective over diabetes control and several cardiovascular risk factors in different populations, with little compelling evidence among Omanis. This paper describes the protocol of a wait-list, open labelled, randomized control trial, with its main objective aimed to determine the effectiveness of Mediterranean Diet intervention on glycaemic control and cardiovascular risks among T2DM patients in Oman. Methods: A total of 140 eligible T2DM patients will be recruited. Participants in the intervention group will undergo a six-month MedDiet program comprising of different activities (individual dietary counseling, cooking classes, phone calls and social media messages) while the control group will continue with standard diabetes care. Data collection will be conducted at baseline, after three and six months. The 2 x 3 mixed-design ANOVA will be used to determine the mean changes in outcome variables over the full study period between the two groups. Discussion: Epidemiology studies on nutrition and health had focused on dietary pattern, which provides an opportunity to account for nutrient-nutrient interactions lately. Mediterranean Diet has produced consistent findings on its protective role in diabetes management, with little information on its effectiveness in population outside of Mediterranean basin, including Oman. The outcomes of current study will be used to inform community and health care professionals on the effectiveness and practically of MedDiet on diabetes management.